Packaging and Shipping of Infectious Materials: Integrated Health Security Governance, Administrative Compliance, Medical Secretariat Coordination, and Pharmacy Technician Logistics - Aloteibi, Fares Nasser; Khalefh Gnem Khalefh Aldosari; Amani Yahya Ebrahim Hazmi ‏; Khulud Awadh Muaysir Alruwaili; Musaed Sadullah Alghamdi; Majed Saad Yahya Alharbi; Abdullah Khalid Salem Alshehri; Hind Hlil Alotaibi; Wejdan Nasser Saad Aldawsari; Hind Mohammed Alqahtani; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The safe transport of infectious substances is a critical biosafety and health security function. Mishandling during packaging or shipping can lead to occupational exposure, environmental contamination, and public health risks. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This paper aims to outline the regulatory frameworks, classification systems, packaging requirements, and operational practices necessary for the safe transport of infectious materials. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of international and U.S. regulatory guidelines, including WHO, UN Model Regulations, DOT Hazardous Materials Regulations, and IATA standards, was conducted. Key operational domains such as classification, packaging, marking, labeling, documentation, and emergency response were analyzed. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Infectious substances are categorized into Category A (high-risk, UN 2814/2900) and Category B (moderate-risk, UN 3373), with exemptions for low-risk specimens. Category A requires UN-certified triple packaging and strict documentation, while Category B mandates robust containment and standardized markings. Training for all stakeholders is essential, with renewal every three years. Emergency preparedness and spill management protocols are integral to risk mitigation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Safe transport of infectious substances demands a unified system integrating regulatory compliance, standardized packaging, competency-based training, and emergency readiness. Adherence to these measures prevents exposure, ensures diagnostic continuity, and strengthens public health resilience.